2014
DOI: 10.4274/khj.64936
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Prevalence of Myocardial Bridging in Our Department

Abstract: Doğumsal bir koroner arter anomalisi olan Miyokardiyal Bridge (MB), epikardiyal koroner arterlerden birinin bir segmentinin miyokardiyum içerisinde seyretmesi ile karakterize bir durumdur. MB tarafından oluşturulan koroner obstrüksiyonun derecesi, MB'nin lokalizasyonuna, kalınlığına, uzunluğuna ve kardiyak kontraktilitenin derecesine bağlıdır. Otopsi çalışmalarında prevalansı %80 kadar yüksek bulunmasına rağmen, koroner anjiografi çalışmalarında prevalansı %0,5 ile %16 arasında değişmektedir. Hastalar ve Yönte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Other factors that may affect the incidence of MB are the size and ethnicity of the study population. The incidence of MB was found to be around 1% in FACCA studies performed in Turkish populations similar in size to the current study [ 16 , 17 ]. In the current study, MB incidences of patients who underwent RACA and FACCA with similar baseline characteristics except for their clinical presentation were compared.…”
Section: Discussionsupporting
confidence: 83%
“…Other factors that may affect the incidence of MB are the size and ethnicity of the study population. The incidence of MB was found to be around 1% in FACCA studies performed in Turkish populations similar in size to the current study [ 16 , 17 ]. In the current study, MB incidences of patients who underwent RACA and FACCA with similar baseline characteristics except for their clinical presentation were compared.…”
Section: Discussionsupporting
confidence: 83%
“…In a study conducted in the Central Anatolia region of our country, the frequency of MB was found to be 0.94% (16). In a similar study conducted in the Eastern Anatolia region, it was found to be 1.1% (17). In a coronary angiography study in which twenty-five thousand nine hundred and eighty-two patients were retrospectively analyzed, MB was detected in a total of 316 patients, and its prevalence was found to be 1.22% in this study (18).…”
Section: Resultssupporting
confidence: 52%
“…21 In studies conducted in Turkish population higher than the size of the current study, the prevalence of MB was reported to be approximately 1%. [21][22][23] Moreover, provocative tests by nitroglycerin and diltiazem might increase the detection rate of MB. 17, 21 Other factors that may affect the variations in the reported prevalence of MBs are the depths of the bridging segment.…”
Section: Discussionmentioning
confidence: 99%